Prähistorische Textilkunst in Mitteleuropa Geschichte des Handwerkes und Kleidung vor den Römern - Grömer, Karina (Naturhistorisches Museum Wien, 2010)
The roots of our history as well as the history of the textile craft reach back to the "dark ages" without written sources, the millennia before the ancient civilisations. Textiles, textile production and clothing were essentials of living in prehistory, locked into the system of society at every level - social, economic and even religious. In Roman Period written sources allow us to draw a colourful picture of textiles and their producers - about work and identity. For prehistory the mearge evidences from archaeological excavations has to be puzzled together. It is a delightful challenge, to create a hypothesis about "the people behind", about textile producers, about the history of clothing. This book is dedicated to historians, costume designers, archaeologists und all persons, who are interested in handcraft and artisanship. We deal with the prehistory in Central Europe, with a special focus on Austrian sites and finds as well as the surrounding countries. Our knowledge for textile production in pre-Roman Europe comes from various sources such as surviving textiles, grave finds, textile tools, archaeological evidences from settlements and depictions of crafts people and their products. From the last centuries before Christ, at the end of Iron Age, we also have sparse written sources. The title of this book "Prehistoric Textile Art" was chosen to point on the skill of prehistoric people to use different patterning techniques. Commonly prehistoric textiles from Europe before the ancient civilisations are thought to be very simple and primitive.The aim of this book is to show the variety of working processes and techniques. It is a fact, that the most important techniques in textile handicraft and art, which we use even in the 21th century, have their roots in prehistoric times. They even reach back to Stone and Bronze Age. During this time human beings created the most important weaving and sewing techniques, weave and pattern types. Especially the Bronze Age innovations, like weaving twill, dyeing textiles or special pattern systems are surprising. There is a well development of textile techniques towards Iron Age. The textile qualities in Hallstatt Period are finer and multifaceted than in the preceding periods. They are rich in colour, as well as in different weave-types, patterns and decorations. There are different styles of band weaves.Usually decorative techniques used in prehistoric times were introduced during weaving. Therefore typical designs of the patterns are connected with the warp and weft system of the weave. For example stripes or checked patterns are woven with warp and/or weft threads of different colours. For curving and circular designs there are different techniques to be used. For Central European prehistory we know of different brocade techniques with floating thread systems. Inserting or attaching different elements into a weave, such as beads or even metal stripes was known. Embroidery, the "small art" beside sewing, was used to create decorative products. Tablet weaving is a special weaving technique utilising four-holed tablets which permits to compose complicated and figurative designs. This technique reached its first zenith during Hallstatt PeriodThis first overview allows us to draw a picture of the development of textile production, starting from household production level in Stone and Bronze Age and culminating in more industrial level workshop production in Roman times. It is important to emphasise that, from Hallstatt Period onwards we know a highly developed textile art and there is evidence of a well organised textile production - on household level and possibly specialised craft and the first mass production in workshops. The textiles and tools show clearly, that there is a continuous development from the beginning of the Iron Age till Roman era. For the topic "work and identity" the crafts people - the textile producers - are in the focus as well as the organisation of the pro